Large Meteorite Impacts and Planetary Evolution; II 1999
DOI: 10.1130/0-8137-2339-6.345
|View full text |Cite
|
Sign up to set email alerts
|

Origin of carbonaceous matter, fullerenes, and elemental sulfur in rocks of the Whitewater Group, Sudbury impact structure, Ontario, Canada

Abstract: New carbon determinations of 20 rocks confirm that both the breccias of the BlackMember of the Onaping Formation and the mudstones of the Onwatin Formation of the Whitewater Group in the 1.8-Ga Sudbury impact structure contain appreciable amounts of carbonaceous matter. The origin of the carbon has been a long-standing enigma. Carbon-bearing target rocks, either carbonaceous mudstones or carbonate target rocks are not its source, and neither is CO 2 from the atmosphere of the impact area, or carbon from the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…[126] Other investigators have failed to find fullerenes in their samples of the same formation. [127] Table 2 T2 lists the results of all searches for fullerenes in rocks from the Sudbury structure. Clearly some samples contained fullerenes whilst others did not.…”
Section: Sudburymentioning
confidence: 99%
See 4 more Smart Citations
“…[126] Other investigators have failed to find fullerenes in their samples of the same formation. [127] Table 2 T2 lists the results of all searches for fullerenes in rocks from the Sudbury structure. Clearly some samples contained fullerenes whilst others did not.…”
Section: Sudburymentioning
confidence: 99%
“…Raman spectra show that the carbon is highly disordered. [127] Various theories about the origin of this carbon exist, but extensive 13 C= 12 C measurements have now conclusively demonstrated that the Black Member carbon is isotopically the same as carbon from the Onwatin and Chelmsford Formations, hence is biogenic. The carbon proper is not from the impactor, but postdates the formation of the crater.…”
Section: Sudburymentioning
confidence: 99%
See 3 more Smart Citations